Clinical and Functional Outcome of Tibialis Anterior Tendon Transfer for Recurrent Clubfoot in a Limited Resource Country: A Three-year Retrospective Cohort Study - Alazar M. Haile, MD; Birhanu Ayana, MD; Wubegzier Mekonnen, PhD; Fentahun Bantigegn, MD; Bizuayehu Amanu, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: Tibialis anterior tendon transfer (TATT) is a surgical procedure aimed at correcting dynamic supination in children with idiopathic clubfoot, typically performed between ages 2.5 and 5. There is limited literature discussing the factors that contribute to unfavorable outcomes. This study explores the clinical and functional outcomes of TATT and identifies factors that lead to poor functional results. Methods: This retrospective cohort study evaluated children with recurrent idiopathic clubfoot who underwent TATT from February 2021 to February 2024 in Tikur Anbessa Specialized Hospital, Ethiopia. A matched comparison group that did not undergo TATT was used, with a final sample of 42 TATT patients (56 feet) and 21 non-surgery patients (36 feet). For cases involving both feet, the outcome scores were averaged. Data were collected using the Oxford Foot Ankle Questionnaire and Pirani/Bohm/Sinclair scores via interviews and clinical evaluations, with analysis performed using the R package vcd (R Core Team, 2024). Results: Sixty-three cases (92 feet) were analyzed. The TATT group showed significantly better clinical (P = .02) and functional scores (P = .006). However, a low correlation was observed between clinical measures and patient-reported outcomes (τ = 0.22, P = .018). Patients with poor brace compliance and structural deformities (varus/equinus) showed inferior patient-reported outcomes on the bivariate regression. A progressive decline in patient-reported outcomes was also noted with advancing patient age at the time of surgery. In multivariate analysis, structural deformities—namely varus (P = .012) and equinus (P < .001)—were significantly related to poor functional outcomes. Conclusions: The TATT group exhibited higher clinical (12.3%) and functional (11.8%) scores compared with the non-TATT group, indicating better outcomes. The low correlation between the two outcome scores (τ = 0.22, P = .018) underscores the importance of a comprehensive patient evaluation prior to surgery. Furthermore, unaddressed concomitant structural deformities, such as varus (P = .012) and equinus (P < .001), were linked to poorer functional outcomes when compared with cases that experienced a recurrence of dynamic supination after TATT (P = .8). Key Concepts: (1) The Ponseti method, which involves serial manipulation and casting, is considered the gold standard for the initial management of idiopathic clubfoot. (2) Approximately one-third of clubfoot cases treated successfully experience a recurrence, often presenting as dynamic supination. (3) For children over the age of three, tibialis anterior tendon transfer is recommended to address dynamic supination. (4) Clinician assessment of the need for the procedure does not always correlate with patient perception of functional impairment. (5) Limited published data suggest that there are significant rates of secondary recurrence even after successful tendon transfer. Levels of Evidence: Level III